'Being part of something much bigger than self': the community play as a model of implicit and explicit political theatre practice. Issue 2 (2nd April 2020) - Weston, Sarah
ABSTRACT: This article focuses on the community play, as conceived by Ann Jellicoe, as a form of political theatre-making. Examining two community play productions: Drummer Hodge (2014) and Love on the Dole (2016), I explore how the form's theatrical conventions combine with the play's content to generate political action. Discussing how the community play has been under-theorised in applied theatre literature, I argue that the form can bring together the more celebratory aspects of community that are present in applied theatre discourses, with explicit political motivations to create political practice in the context of twenty-first century austerity.